Meteo–geographical data input tools used with ATD Demokritos code. (4th August 2014) - Deligiannis, P.; Catsaros, N.; Varvayanni, M.; Bartzis, J.G.
Geographical and meteorological data input tools used with the Demokritos atmospheric transport dispersion code system are specifically designed for dispersion computations over complex terrain. The code initialisation depends mainly on the topography simulator (DELTA), which provides detailed information with respect to orography, land–cover, roughness and inclination, orientation and area of the individual ground surfaces, simulating the real topography. The meteorological input data can be provided by regional simulation codes and/or meteorological stations. In both above–mentioned cases, meteorological pre–processing (FILMAKER) is vital for improving the performance of the dispersion model. For each point of interest, the existing meteorological measurements are taken into account with region characterisation based on meteorological coherence. A hierarchical treatment is then established by treating first calculation points belonging to one of the above regions using local 'significant' meteorological measurements and taking into account the time of the year and day. A standard 1/r n interpolation scheme is then used for the remaining calculation points. The method has been successfully tested against real field experimental data.